Control of Ochratoxin A production in grapes - Ponsone, María Lorena; Chiotta, María Laura; Palazzini, Juan Manuel; Combina, Mariana; Chulze, Sofia Noemí (2017)
Ochratoxin A (OTA) is a mycotoxin commonly present in cereals, grapes, coffee, spices, and cocoa. Even though the main objective of the food and feed chain processors and distributors is to avoid the extended contamination of plant-derived foods and animal feeds with mycotoxins, until now, complete OTA removal from foods and feedstuffs is not feasible. Prevention through pre-harvest management is the best method for controlling mycotoxin contamination. However, in the case that the contamination occurs after this stage, the hazards associated with OTA must be managed through post-harvest strategies. Due to the increasing number of fungal strains resistant to chemical fungicides and the impact of these pesticides on the environment and human health, maximum levels of chemical residues have been regulated in many products. Alternative methods are necessary to substitute or complement treatments with fungicides to control fungi under field or storage conditions. Yeasts are considered one of the most potent biocontrol agents due to their biology and non-toxic properties. Epiphytic yeasts are the major component of the microbial community on the surface of grape berries and they are evolutionarily adapted to this ecological niche. Nowadays, several yeast species included in different genera are considered as potential biocontrol agents to control both, growth of ochratoxigenic Aspergillus species and OTA accumulation